2018
DOI: 10.1111/bph.14139
|View full text |Cite
|
Sign up to set email alerts
|

The natural compound, formononetin, extracted from Astragalus membranaceus increases adipocyte thermogenesis by modulating PPARγ activity

Abstract: Taken together, our study demonstrates that the Chinese herbal medicine from A. membranaceus and its constituent formononetin have the potential to reduce obesity and associated metabolic disorders. Our results suggest that formononetin regulates adipocyte thermogenesis as a non-classical PPARγ agonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Identification of the possible mechanism of action of the natural product is mandatory for publication in BJP. As an example in which evaluation of an extract was followed by a detailed pharmacological analysis of the main active ingredient, a BJP paper reported that multiple distinct Chinese herbal medicine extracts increased the expression of uncoupling protein 1 in isolated adipocytes (Nie et al, 2018). The authors found that extracts from the Chinese plant Astragalus membranaceous had the highest activity and then went on to isolate and purify the components of that extract (with data from HPLC identifying the constituents).…”
Section: Papers Promoting a Phytochemical As Lead Compound For The Dementioning
confidence: 99%
“…Identification of the possible mechanism of action of the natural product is mandatory for publication in BJP. As an example in which evaluation of an extract was followed by a detailed pharmacological analysis of the main active ingredient, a BJP paper reported that multiple distinct Chinese herbal medicine extracts increased the expression of uncoupling protein 1 in isolated adipocytes (Nie et al, 2018). The authors found that extracts from the Chinese plant Astragalus membranaceous had the highest activity and then went on to isolate and purify the components of that extract (with data from HPLC identifying the constituents).…”
Section: Papers Promoting a Phytochemical As Lead Compound For The Dementioning
confidence: 99%
“…Formononetin is a principal isoflavone compound extracted from Radix Astragali , which has long been used to treat cardiovascular diseases in traditional Chinese medicine. For example, formononetin has been reported to be able to reduce intracellular ROS by inhibiting mitogen activated protein kinase 8 phosphorylation ( 28 ); to inhibit breast cancer cell proliferation by regulating the phosphatidylinositol 3-kinase (PI3K)/RAC-α serine/threonine-protein kinase (AKT)/serine/threonine-protein kinase mTOR signaling pathway ( 29 ); to increase adipocyte thermogenesis by modulating peroxisome proliferator-activated receptor-γ activity ( 30 ); or to have neuroprotective effects following traumatic brain injury by increasing microRNA-155 and heme oxygenase-1 expression ( 31 ). Regarding I/R injury, formononetin has been reported to markedly reduce the infarct volume and brain water accumulation in a rat model of I/R injury via activation of the PI3K/Akt signaling pathway ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both diets rich in isoflavones and the administration of daidzein were found to result in the increased expression of uncoupling protein 1 (ucp1), a thermogenic marker, in the BAT of experimental animals [77,78]. Additionally, formononetin, via direct interaction with PPARγ, was found to increase the expression of ucp1 in primary cultures of mouse adipocytes, while its administration to C57BL/6J mice was found to prevent the development of diet-induced obesity [79]. Similarly, a two-week treatment with coumestrol was found to reduce body weight and improved glucose tolerance in mice on an HFD due to the increased thermogenesis in BAT.…”
Section: Adipose Tissue Browningmentioning
confidence: 99%